Comparative Analysis of the Nutrient Requirements among Yersinia pestis Strains of the Main and Non-Main Subspecies as well as Genetic Causes of Their Auxotrophy - L. M. Kukleva; G. N. Odinokov; N. Yu. Shavina; G. A. Eroshenko; V. V. Kutyrev (Проблемы особо опасных инфекций, 2013)
Studied is the nutrient demand for growth factors among 185 Yersinia pestis strains of the main and non-main subspecies ( altaica, caucasica, hissarica , and ulegeica ) isolated in 38 natural plague foci of Russia and neighboring states. Revealed is the fact that all the strains of Yersinia pestis main subspecies manifest equal dependence in growth on three amino-acids such as methionine, phenylalanine, and threonine, while strains isolated from certain natural foci have an additional demand for cysteine, leucine, and arginine. Strains of non-main subspecies differ in their nutrient requirements both from the strains of the main subspecies and among themselves. Strains of subspecies caucasica stand in need of thiamine and such amino-acids as phenylalanine, tyrosine and arginine; subspecies altaica – phenylalanine, arginine and leucine; subspecies hissarica – phenylalanine, leucine and methionine; ulegeica – phenylalanine. Detected is a number of mutations that lead to auxotrophy in Yersinia pestis strains of different subspecies.